2016
DOI: 10.1016/j.yjmcc.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo pathway mediates inhibition of vascular smooth muscle cell proliferation by cAMP

Abstract: AimsInhibition of vascular smooth muscle cell (VSMC) proliferation by intracellular cAMP prevents excessive neointima formation and hence angioplasty restenosis and vein-graft failure. These protective effects are mediated via actin-cytoskeleton remodelling and subsequent regulation of gene expression by mechanisms that are incompletely understood. Here we investigated the role of components of the growth-regulatory Hippo pathway, specifically the transcription factor TEAD and its co-factors YAP and TAZ in VSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 51 publications
5
62
2
Order By: Relevance
“…An elegant study by Wang et al 36 has recently shown that YAP expression is significantly increased after carotid artery injury, and deletion of YAP attenuates injury-induced neointima formation, which represent an early phase of atherosclerosis. In agreement with this finding, a more recent study has shown that YAP and TAZ are essential for smooth muscle cell proliferation which can be inhibited by YAP inhibitor verteporfin as well as agents that elevate intracellular cyclic AMP levels 37 . Our present study found that atheroprotective LF triggered YAP phosphorylation and decrease YAP nuclear expression, consequently decreased the expression of mechanosensory YAP target genes (CTGF and Cyr61 etc) 38, 39 in ECs.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…An elegant study by Wang et al 36 has recently shown that YAP expression is significantly increased after carotid artery injury, and deletion of YAP attenuates injury-induced neointima formation, which represent an early phase of atherosclerosis. In agreement with this finding, a more recent study has shown that YAP and TAZ are essential for smooth muscle cell proliferation which can be inhibited by YAP inhibitor verteporfin as well as agents that elevate intracellular cyclic AMP levels 37 . Our present study found that atheroprotective LF triggered YAP phosphorylation and decrease YAP nuclear expression, consequently decreased the expression of mechanosensory YAP target genes (CTGF and Cyr61 etc) 38, 39 in ECs.…”
Section: Discussionsupporting
confidence: 68%
“…It can be anticipated that by use of high content screening or high throughput screening of FDA-approved drug library or natural compounds library, more and more novel and specific YAP inhibitors will be developed for treating various human diseases in the future. In terms of the vasculature, emerging evidence suggests that YAP is also critical for cardiovascular development and diseases 36, 37, 47, 5457 . Whether genetic deletion of YAP in ECs or pharmacological inhibition of YAP activity could prevent the development of atherosclerosis in preclinical settings warrants further studies.…”
Section: Discussionmentioning
confidence: 99%
“…C-myc has been reported as the target gene of TAZ and TEAD [17, 25]. We have shown that the expression of C-myc is consistent with the level of TAZ, so TAZ might promote glioma progression through activation of C-myc.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, in the present study, we tested several doses of verteporfin, which have also been used in previously published articles. 34,35 Before treatment, cells were starved overnight in serum-free Dulbecco's Modified Eagle's Medium (DMEM; Wako Pure Chemical Industries, Osaka, Japan).…”
Section: Cell Stimulationmentioning
confidence: 99%